Additive manufacturing of hierarchical injectable scaffolds for tissue engineering. (August 2018) - Béduer, A.; Piacentini, N.; Aeberli, L.; Da Silva, A.; Verheyen, C.A.; Bonini, F.; Rochat, A.; Filippova, A.; Serex, L.; Renaud, P.; Braschler, T.
Graphical abstract: Abstract: We present a 3D-printing technology allowing free-form fabrication of centimetre-scale injectable structures for minimally invasive delivery. They result from the combination of 3D printing onto a cryogenic substrate and optimisation of carboxymethylcellulose-based cryogel inks. The resulting highly porous and elastic cryogels are biocompatible, and allow for protection of cell viability during compression for injection. Implanted into the murine subcutaneous space, they are colonized with a loose fibrovascular tissue with minimal signs of inflammation and remain encapsulation-free at three months. Finally, we vary local pore size through control of the substrate temperature during cryogenic printing. This enables control over local cell seeding density in vitro and over vascularization density in cell-free scaffolds in vivo . In sum, we address the need for 3D-bioprinting of large, yet injectable and highly biocompatible scaffolds and show modulation of the local response through control over local pore size. Statement of Significance: This work combines the power of 3D additive manufacturing with clinically advantageous minimally invasive delivery. We obtain porous, highly compressible and mechanically rugged structures by optimizing a cryogenic 3D printing process. Only a basic commercial 3D printer and elementary control over reaction rate and freezing are required. The porous hydrogels obtained are capable of withstanding delivery through capillaries up to 50 times smaller than their largest linear dimension, an as yet unprecedented compression ratio. Cells seeded onto the hydrogels are protected during compression. The hydrogel structures further exhibit excellent biocompatibility 3 months after subcutaneous injection into mice. We finally demonstrate that local modulation of pore size grants control over vascularization density in vivo . This provides proof-of-principle that meaningful biological information can be encoded during the 3D printing process, deploying its effect after minimally invasive implantation.